English Deutsch Français Italiano Español Português 繁體中文 Bahasa Indonesia Tiếng Việt ภาษาไทย
All categories

Differentiate.
y=e^(6 x)/(1+3 x)
y'(x)=

Differentiate.
g(x) = 3sqrt(x)e^x
g'(x)=

2007-10-01 09:58:25 · 2 answers · asked by Anonymous in Science & Mathematics Mathematics

2 answers

y=e^(6 x)/(1+3 x) Use quotient Rule
y'(x)= [(1+3x)(6e^(6x))-3e^(6x)]/(1+3x)^2
y' = (3e^(6x))(1+6x)/(1+3x^2)

g(x) = 3sqrt(x)e^x Use product rule
g'(x)=3sqrt(x)e^x + e^x(-1/2sqrt(x))
= e^x(3sqrt(x) -1/(2sqrt(x)))

2007-10-01 10:14:28 · answer #1 · answered by ironduke8159 7 · 0 0

Its like your are speaking another launguage called numbers

2007-10-01 17:02:43 · answer #2 · answered by Sea♥Turtle 3 · 0 0

fedest.com, questions and answers